2019
DOI: 10.1016/j.conbuildmat.2019.04.259
|View full text |Cite
|
Sign up to set email alerts
|

Steel-Reinforced Grout (SRG) strengthening of shear-critical RC beams

Abstract: This paper investigates the effectiveness of Steel-Reinforced Grout (SRG) jackets to strengthen shear critical reinforced concrete (RC) beams. Eleven RC beams were tested in three-point bending. Key parameters of investigation were the strengthening configuration (Uand fully-wrapped jackets), the density of the fabric (1.57 and 4.72 cords/cm) and the number of the strengthening layers (one and two). The test results demonstrated the efficiency of SRG jacketing in increasing both strength (up to 160%) and defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 35 publications
(54 reference statements)
1
18
0
Order By: Relevance
“…Therefore, U-wraps associated with mechanical anchorage are usually used. The effectiveness of mechanical anchoring has been confirmed by the studies of Mitoldis [59], Papakonstantinou [60], Vakjira [61], and Thermou [62]. Only Gonzales [63] did not report a significant increase in shear strength.…”
Section: Shear Strengthening Of Beamsmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, U-wraps associated with mechanical anchorage are usually used. The effectiveness of mechanical anchoring has been confirmed by the studies of Mitoldis [59], Papakonstantinou [60], Vakjira [61], and Thermou [62]. Only Gonzales [63] did not report a significant increase in shear strength.…”
Section: Shear Strengthening Of Beamsmentioning
confidence: 83%
“…The failure mode depends on the intensity of strengthening. A fully wrapped strong reinforcement moves the failure into the flexure zone [62]. A single-layered and fully wrapped beam fails due to the presence of a shear-flexure crack.…”
Section: Shear Strengthening Of Beamsmentioning
confidence: 99%
“…In all these studies, a considerable improvement in terms of load-bearing capacity was observed. Thermou et al [16] performed shear tests on SRG reinforced concrete beams; from the results obtained, they assessed that SRGs effectively improve the shear capacity and the ductility of RC beams. For the beams strengthened with SRG U-wraps, a drastic improvement was observed; the ultimate load was 104% higher than that observed on the un-strengthened beam.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, research on the application of this technique for strengthening shear deficient beams is scarce. [41][42][43] In addition, previous studies focused on the use of an SRG system for EB strengthening. The failure of EB-SRG strengthened beams, similar to that of EB-FRCM, is mostly attributed to SRG debonding.…”
Section: Introductionmentioning
confidence: 99%